Xist condensates: perspectives for therapeutic intervention - Irene Perotti; Laura Broglia; Gian Gaetano Tartaglia; Andrea Cerase (Genome Biology)
Abstract X-chromosome inactivation (XCI) is a crucial mechanism of dosage compensation in female mammals ensuring that genes from only one X chromosome are expressed, initiated through expression of the long noncoding RNA Xist. Recent evidence underscores the significance of molecular crowding—most likely via liquid–liquid phase separation (LLPS)—in forming Xist RNA-driven condensates critical for establishing and sustaining the silenced state. By integrating existing knowledge and emerging ideas, we provide a comprehensive perspective on the molecular underpinnings of XCI and outline how manipulation of LLPS-based mechanisms offers new avenues for novel therapeutic approaches.